2008
DOI: 10.1038/labinvest.2008.50
|View full text |Cite
|
Sign up to set email alerts
|

Human hepatocellular carcinoma expresses specific PCNA isoforms: an in vivo and in vitro evaluation

Abstract: Proliferating cell nuclear antigen (PCNA) is a 36 kDa protein involved in several cellular mechanisms, including DNA synthesis and repair, cell cycle regulation and apoptosis. An alteration in PCNA structure might contribute to DNA-damage accumulation in cancer cells. This study was aimed to evaluate the PCNA pattern of expression, in terms of aggregation status, isoforms and post-translational modifications, in human hepatocellular carcinoma (HCC) and cirrhosis as well as in HCC cell lines. Twelve HCCs and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…These malignant cells harbor an additional isoform of PCNA with an acidic pI, as opposed to the normal cells, which only contain PCNA with a basic pI. Similar PCNA profiles are present in other types of cancer, including neuroblastoma (Sandoval et al, 2005), hepatic carcinoma (Venturi et al, 2008), and high-grade prostatic intraepithelial neoplasia and prostate cancer (Wang et al, 2011). The newly identified cancer-associated acidic isoform of PCNA (caPCNA) results from a set of post-translational modifications .…”
Section: Introductionmentioning
confidence: 89%
“…These malignant cells harbor an additional isoform of PCNA with an acidic pI, as opposed to the normal cells, which only contain PCNA with a basic pI. Similar PCNA profiles are present in other types of cancer, including neuroblastoma (Sandoval et al, 2005), hepatic carcinoma (Venturi et al, 2008), and high-grade prostatic intraepithelial neoplasia and prostate cancer (Wang et al, 2011). The newly identified cancer-associated acidic isoform of PCNA (caPCNA) results from a set of post-translational modifications .…”
Section: Introductionmentioning
confidence: 89%
“…9 Two-dimensional PAGE analysis illustrated that malignant breast cells harbored an additional isoform of PCNA with an acidic isoelectric point (pI), as opposed to the normal cell expressing PCNA with only a basic pI. The two distinct PCNA isoforms have been resolved in a variety of cancer cell lines, including neuroblastoma, 10 hepatic carcinoma, 11 high-grade prostatic intraepithelial neoplasia and prostate cancer. 12 The acidic isoform associated with cancer (caPCNA) is not the result of genetic mutations or alternate splicing, but is the result of differential post-translational modification within the PCNA molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Venturi et al reported the detection of two PCNA expression patterns in human liver tumors and cell lines [70]. The different pools of PCNA might act together and at the same time to carry out different functions within different signaling pathways, as reported previously [71].…”
Section: Discussionmentioning
confidence: 79%
“…Taken together, during cell cycle arrest, PCNA protein may form complexes with several proteins (p21, p57, Gadd45, MyD118, CR6, ING1, MCL1, MutS α , and MutL α ). PCNA functions and interactions are modulated by posttranslational regulation which is thought to guide PCNA to the correct partner protein at the correct time to perform a specific function [70]. Studies suggest that PCNA is the supervisory molecule in life of the cell, forcing it to replicate DNA, arrest the cell in G1 or G2 phase, repair damaged DNA, or obligate the cell to apoptosis, based on the interactions with a plethora of proteins [72].…”
Section: Discussionmentioning
confidence: 99%